1995
DOI: 10.1139/m95-076
|View full text |Cite
|
Sign up to set email alerts
|

Repression of motility and flagellin production at 37 °C is stronger inListeria monocytogenesthan in the nonpathogenic speciesListeria innocua

Abstract: Listeria monocytogenes and Listeria innocua differ markedly in virulence but are indistinguishable by classical taxonomic criteria. Both species are actively motile and produce abundant flagellin at 22 degrees C. We have found, however, noticeable differences between L. monocytogenes and L. innocua in motility and flagellin production at 37 degrees C. At this temperature, L. monocytogenes strains were virtually nonmotile and produced little or no detectable flagellin, whereas strains of L. innocua were frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…At 25°C, L. monocytogenes is actively motile, with four to six peritrichous cells (40), and produces abundant flagellin (flaA encoded). In contrast, at 37°C, it is virtually nonmotile and produces little or no detectable flagellin (22). Here, we have identified two potential flagellar genes of L. monocytogenes: lmo0713, encoding a protein of 551 amino acids having 23% identity (and 45% similarity) with FliF of B. subtilis, the first structure to be assembled during flagellar biogenesis (23); and lmo0716, encoding a protein of 434 amino acids, having 43% amino acid identity (and 62% similarity) with FliI, an ATPase of B. subtilis that drives flagellar protein export.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…At 25°C, L. monocytogenes is actively motile, with four to six peritrichous cells (40), and produces abundant flagellin (flaA encoded). In contrast, at 37°C, it is virtually nonmotile and produces little or no detectable flagellin (22). Here, we have identified two potential flagellar genes of L. monocytogenes: lmo0713, encoding a protein of 551 amino acids having 23% identity (and 45% similarity) with FliF of B. subtilis, the first structure to be assembled during flagellar biogenesis (23); and lmo0716, encoding a protein of 434 amino acids, having 43% amino acid identity (and 62% similarity) with FliI, an ATPase of B. subtilis that drives flagellar protein export.…”
Section: Resultsmentioning
confidence: 95%
“…At each condition tested, the ⌬fliF and ⌬fliI mutant strains exhibited a normal colony morphology on solid medium and a growth rate identical to that of the wild-type strain EGD-e in liquid medium (data not shown). The two mutants were assayed for mobility in semisolid BHI medium, as described by Kathariou and coworkers (22). The ability to swim is thought to be a ubiquitous behavioral trait exhibited by flagellated eubacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Swarming on soft agar was analyzed as described by Kathariou et al (30), with some modifications. Individual colonies were transferred to a petri plate containing tryptic soy broth (Difco) with 0.25% agar, and the motility plates were incubated for 24 h at 24 or 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…This temperature regulation might serve as a mechanism to evade recognition by the innate immune system in the host. Interestingly, when comparing L. monocytogenes with the nonpathogenic but closely related species L. innocua, Kathariou et al (30) found that the repression of flagellin in L. innocua was not as strong as the repression in L. monocytogenes. The discrepancy of the in vivo virulence test of the ⌬flaA mutant with the in vitro invasion experiments with this mutant can be reconciled through the observation that the ⌬flaA mutant were present at lower levels than WT bacteria in TNFR-p55 Ϫ/Ϫ mice.…”
Section: Fig 6 Cfu After Ig Infection Of Tnfr-p55mentioning
confidence: 99%
“…Bacterial swimming was investigated on swim plates as described elsewhere (Kathariou et al, 1995;Knudsen et al, 2004). Single colonies were inoculated in Tryptic Soy Broth (TSB) with 0.25 % agar and incubated at either 25 or 37 uC for 48 h.…”
mentioning
confidence: 99%